Influence of Project Managers Perception on The Success of Projects in Relation To Early Engagement of contractors And Suppliers - ALYAN, WAEL SALEEM (2018)
The innovation in project management is highly required due to the massive expansion in project’s sizes, values, functionalities and complexity. The projects are now a days being faced by plenty of challenges in terms of the high competition, confined budgets, multiple functions and high expectations by investors. Moreover, the adoption of the innovation in construction field is relatively weak in comparison with the other industries. Hence, this research aims to add value to the existing literature about the influence of project manager perceptions factors on project success in relation of early engagement of contractors and suppliers procurement strategy. 13 factors of project managers perception and 9 factors of early engagement influence to the projects success were illustrated in this research. This quantitative method was used in this research via online survey the targeted respondents were from the constructional projects field. The collected data were tested and found valid and reliable. SPSS software was used to display the analysis. The participants in this survey are relevant to the research topic. The findings demonstrate an influence of project manager perceptions to project success in relation to the implementation of early engagement of contractors and suppliers as an innovative procurement. Accordingly, the constructional projects concerned entities such as the clients, developers, authorities, consultants and contractors are advised to adopt such innovative procurement strategy and improve the project managers perception to secure best implementation of this innovative approach to reap the best outcome.